Relationships between maximum strength, sprint ability and rate of increase in sprint time in 20 m sled towing - Martinez-Valencia, M. A.; Cánovas, J. F.; Romero-Arenas, S.; Linthorne, N. P.; Gonzalez-Rave, J. M.; Alcaraz, P. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Towing sled is one of many methods that have been implicated in the development of running speed, in this sense, it has been suggested that resisted sprint towing increases athletes strength (Alcaraz et al., 2008). In this training method the load is adjusted to set the intensity of the exercise, and this weight is often set to a percentage of the athletes body mass (Bm). Other authors (Murray et al., 2005) suggested that the athletes sprint time increased linearly with increasing sled mass, but we hypothesized that the effect of the sled mass on athletes sprint ability depends on strength or power variables. According to this suggestion, previous study (Murray et al., 2005) proposed assigning loads as a proportion of strength. In this respect, the aim of the study was to determine the relationship between maximum strength, sprint ability and rate of increase in sprint time. Methods: Nine men active competitive athletes specialized in sprinting were recruited for the study (22.6 ± 4.0 years, 1.83 ± 0.04 m, and 72.4 ± 8.0 kg). The participants performed two tests in two days. The first day, 1-RM from a half-squat position, the last acceptable single repetition with the highest possible load was recorded. This load was also normalized by dividing by the participants Bm. 48 hours after, seven 20-m sprints (unloaded sprints and sprints pulling resistances of 5, 10, 15, 20, 25 and 30% of Bm) from a standing start were done. The participants were placed 1-m behind the starting line. The resisted sprint trials were performed using a weighted sled attached to each athlete by a 2.7-m cord and waist harness, and an unlimited rest period was given between trials to minimize the effects of fatigue. The participants unloaded and loaded sprint time were plotted against the load (%Bm), obtaining a straight line (y = mx + c), the gradient of the line of best fit (m) was taken as the rate of increase in sprint time. Results: A Pearsons Product moment correlation coefficient showed that there was no significant association (p . 0.05) between 1 RM, also 1 RM/Bm, and rate of increase (1.80 ± 0.36 seconds per body mass). However, a significant correlation was found between unloaded sprint time and rate of increase (r = -0.74). Discussion: The lack of correlation to 1 RM may be explained by the stage of the season, the test was conducted at the end of the season. The effects of the sled-towing exercises on athletes velocity profile may be due to the athletes sprint ability in 20-m, suggesting that sled mass may be applied taking into account the individual sprint level of the athlete.